Associations of moderate to vigorous physical activity and sedentary behavior with depressive and anxiety symptoms in self-isolating people during the COVID-19 pandemic: A cross-sectional survey in Brazil. (October 2020) - Schuch, Felipe B.; Bulzing, Rugero A.; Meyer, Jacob; Vancampfort, Davy; Firth, Joseph; Stubbs, Brendon; Grabovac, Igor; Willeit, Peter; Tavares, Vagner Deuel O.; Calegaro, Vitor C.; Deenik, Jeroen; López-Sánchez, Guillermo F.; et al.
Highlights: Nearly half of the participants spent more than 30 min per day in moderate to vigorous physical activity (MVPA). One-third of the participants spent more than 10 h per day sitting. Those reporting over 30 min of MVPA/day were less likely to present depressive, anxiety, or co-occurring depressive and anxiety symptoms. Those reporting over 10 h sitting/day were more likely to present depressive symptoms. Abstract: This is a cross-sectional study evaluating the associations of self-reported moderate to vigorous physical activity, and sedentary behavior with depressive, anxiety, and co-occurring depressive and anxiety symptoms (D&A) in self-isolating Brazilians during the COVID-19 pandemic. Depressive and anxiety symptoms were collected using the Beck Depression and Anxiety Inventories (BDI and BAI). Among the 937 participants (females=72.3%), those performing ≥30 min/day of moderate to vigorous or ≥15 min/day of vigorous physical activity had lower odds of prevalent depressive, anxiety, and co-occurring D&A symptoms. Those spending ≥10 h/day sedentary were more likely to have depressive symptoms.